2011
DOI: 10.1007/s00431-011-1504-8
|View full text |Cite
|
Sign up to set email alerts
|

Familial hypocalciuric hypercalcemia: new mutation in the CASR gene converting valine 697 to methionine

Abstract: Familial hypocalciuric hypercalcemia is an uncommon cause of hypercalcemia that arises from mutations in the calcium-sensing receptor gene. Inactivation of this receptor leads to a decreased receptor sensitivity to calcium, determining that higher concentrations of calcium are needed to inhibit the release of parathormone in the parathyroid glands. Patients usually are asymptomatic. Diagnosis is usually made casually after a routine blood analysis. The syndrome is characterized by mild or moderate hypercalcemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…In concordance with other studies, we found both inactivating (p.Cys677Tyr, p.Val697Met, p.Phe789del, p.Ile816Val and p.Ile816Thr) and activating (p.Phe788Cys, p.Ser820Phe and p.Gly830Ser) mutations in the transmembrane domain (19,20).…”
Section: :1 66 Clinical Studysupporting
confidence: 93%
“…In concordance with other studies, we found both inactivating (p.Cys677Tyr, p.Val697Met, p.Phe789del, p.Ile816Val and p.Ile816Thr) and activating (p.Phe788Cys, p.Ser820Phe and p.Gly830Ser) mutations in the transmembrane domain (19,20).…”
Section: :1 66 Clinical Studysupporting
confidence: 93%